Entrance, Britannia and Co. - Ghosh, Ayan (2023)
Located on the ground floor of Wakefield House, Britannia and Co. was founded (1923) by Rashid Kohinoor, who had emigrated from Iran to Mumbai in search of a better life. His son and Britannia's long-time owner, Boman Kohinoor (1923-2019), was proud of the cafe’s historic link to Britain and its royal family. He called himself the ‘Royal Family’s No.1 fan’.